2007
DOI: 10.1111/j.1365-2249.2007.03365.x
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolism and indoleamine 2,3-dioxygenase expression in coeliac disease

Abstract: SummaryWe have investigated the possible role of the metabolism of tryptophan and activity of the enzyme indoleamine 2,3-dioxygenase (IDO) in the immune regulation of coeliac disease (CD). Serum concentrations of tryptophan and its metabolites kinurenines were determined by high performance liquid chromatography in 24 patients with CD, seven patients with Crohn's disease and five healthy patients. We detected an increase of kynurenine (4·2 mmol/l Ϯ 0·27 versus 2·6 mmol/l Ϯ 0·54, P < 0002) and of the kynurenine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…Elevated levels of neopterin, as well as other monocyte/ macrophage cytokines, in patients with AAV during active disease and remission have also been reported by other groups (13,20,30). Alterations in tryptophan and its metabolites have been shown to contribute to immune regulation in maternal-fetal tolerance (31) and in renal transplant recipients (32), as well as in other autoimmune diseases (33,34). Tryptophan degradation and kynurenine generation are associated with T cell hyporesponsiveness and apoptosis.…”
Section: Discussionmentioning
confidence: 68%
“…Elevated levels of neopterin, as well as other monocyte/ macrophage cytokines, in patients with AAV during active disease and remission have also been reported by other groups (13,20,30). Alterations in tryptophan and its metabolites have been shown to contribute to immune regulation in maternal-fetal tolerance (31) and in renal transplant recipients (32), as well as in other autoimmune diseases (33,34). Tryptophan degradation and kynurenine generation are associated with T cell hyporesponsiveness and apoptosis.…”
Section: Discussionmentioning
confidence: 68%
“…In the mouse gut, IDO expression is the highest in the small intestine and is ∼10-fold lower in the cecum and colon (10). Previous studies have shown that IDO expression is elevated in a number of intestinal inflammatory conditions, including ulcerative colitis, Crohn's disease, and celiac disease (25,26), suggesting a need for further investigation of the role of IDO in intestinal inflammation. In this regard, Gurtner et al (15) showed that the IDO inhibitor 1-mT significantly increased the severity of TNBS-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan metabolism has been linked to autoimmune disorders associated with inflammation and immune activation [44] . The expression of key genes (Indo and Wars) in tryptophan oxidation increased in the inflamed colon of Il10 -/-mice fed the OA diet.…”
Section: Inflammation and Tryptophan Metabolismmentioning
confidence: 99%